Aires : Luz y Sombra de Las Palmas de Gran Canaria. - Centro Atlántico de Arte Moderno, Las Palmas de Gran Canaria; Museo Internacional de Arte Contemporaneo, Lanzarote; Fernández, Horacio; Vaquero, José Luis Gago; Williams, Rosalind (Las Palmas de Gran Canaria : Centro Atlantico de Arte Moderno, 1999)
Aldai, Angel Luis ; Andrada, Genin ; Bergasa, Miguel ; Blassi, Jaume ; Echeverria, Juan ; Gonçalves, Tato ; Herraez, Fernando ; Müller-Pohle, Andreas ; Perez, Bernardo ; Rio Branco, Miguel ; Schwartz, Carlos A. ; Solana, Andres
biografie
Aires : Luz y Sombra de Las Palmas de Gran Canaria, Centro Atlantico de Arte Moderno, Las Palmas, 14 diciembre 1999 - 20 febrero 2000 / Museo Internacional de Arte Contemporaneo, Lanzarote, 9 marzo 2000 - 13 mayo 2000
Engels
Spaans
boek